Novel DNA methylation loci and genes showing pleiotropic association with Alzheimer’s dementia: a network Mendelian randomization analysis - Di Liu; Youxin Wang; Huiquan Jing; Qun Meng; Jingyun Yang (Epigenetics, 2022)
Previous genome-wide association studies (GWAS) have identified potential genetic variants involved in the risk of Alzheimer’s dementia, but their underlying biological interpretation remains largely unclear. In addition, the effects of DNA methylation and gene expression on Alzheimer’s dementia are not well understood. A network summary data-based Mendelian randomization (SMR) analysis was performed integrating cis- DNA methylation quantitative trait loci (mQTL) /cis- gene expression QTL (eQTL) data in the brain and blood, as well as GWAS summarized data for Alzheimer’s dementia to evaluate the pleiotropic associations of DNA methylation and gene expression with Alzheimer’s dementia and to explore the complex mechanisms underpinning Alzheimer’s dementia. After correction for multiple testing (false discovery rate [FDR] P < 0.05) and filtering using the heterogeneity in dependent instruments (HEIDI) test (PHEIDI>0.01), we identified dozens of DNA methylation sites and genes showing pleiotropic associations with Alzheimer’s dementia. We found 22 and 16 potentially causal pathways of Alzheimer’s dementia (i.e., SNP→DNA methylation→Gene expression→Alzheimer’s dementia) in the brain and blood, respectively. Approximately two-thirds of the identified DNA methylation sites had an influence on gene expression and the expression of almost all the identified genes was regulated by DNA methylation. Our network SMR analysis provided evidence supporting the pleiotropic association of some novel DNA methylation sites and genes with Alzheimer’s dementia and revealed possible causal pathways underlying the pathogenesis of Alzheimer’s dementia. Our findings shed light on the role of DNA methylation in gene expression and in the development of Alzheimer’s dementia.